Bis(mu-quinoline-2-carboxylato)-kappa 3 N,O:O;kappa 3 O:N,O-bis[(acetato-kappa 2 O,O')(methanol-kappa O)lead(II)] - Mohammadnezhad, G.; Ghanbarpour, A.R.; Amini, M.M.; Ng, S.W. (International Union of Crystallography, 2010)
The dinuclear title compound, [Pb(2)(C(10)H(6)NO(2))(2)(CH(3)COO)(2)(CH(3)OH)(2)], lies across an inversion center. The methanol-coordinated PbII atom is chelated by the acetate anion as well as by the quinoline-2-carboxylate anion. One O atom of the quinoline-2-carboxylate anion bridges two symmetry-related PbII atoms, forming the dinuclear compound. Aside from the six atoms connected to the PbII atom by regular coordination bonds, the structure features a long Pb...O interaction [3.145 (3) A] that gives rise to a distorted Psi-square-antiprismatic geometry at the metal center. The H atom of the methanol is hydrogen bonded to an O atom of the acetate.